Reproductive Outcomes of in Vitro Fertilization and Embryo Transfer in Women with Unexplained Repeated Implantation Failure are Significantly Improved with Intravenous Immunoglobulins - Mingming Shu; Yujuan Zhou; Hong Liang; Huimin Han; Wei Zhong; Shun Yao; Zhuolin Ruan; Ding Yu; Wei Shang (Clinical and Experimental Obstetrics & Gynecology)
Background: The aim of this study was to investigate the effects of intravenous immunoglobulins (IVIg) in the immunotherapy of in vitro fertilization and embryo transfer (IVF-ET) patients and to provide insights into the treatment strategy for implantation failure. Methods: A retrospective observational study of 245 patients with unexplained repeated implantation failure in our hospital from 2016 to 2021 was conducted. Among these patients, 124 were administered IVIg according to their preferences during the preparation of implantation, while the others were not given IVIg as a control group. The basic characteristics of the patients in the two groups did not show any significant differences. Biochemical pregnancy rate, clinical pregnancy rate, and live birth rate were compared in the two groups, and also in the IVIg group and the control group, by age (<40 years old and ≥40 years old). Results: The biochemical pregnancy rate, clinical pregnancy rate, and live birth rate in the IVIg group were significantly higher (p < 0.05) than in the control group. However, it was found that there were no significant differences in the reproductive outcomes between the IVIg group and the control group for patients older than 40 years. While for the patients less than 40 years old, the biochemical pregnancy rate, clinical pregnancy rate, and live birth rate of the IVIg group were all higher than those of the control group (p < 0.05). Conclusions: The results of this study suggest that IVIg treatment had a better reproductive outcome for IVF-ET patients with unexplained repeated implantation failure, particularly for patients under age 40.